2011
DOI: 10.1038/nmeth.1569
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput single-molecule optofluidic analysis

Abstract: We describe a high-throughput, automated single-molecule measurement system, equipped with microfluidics. the microfluidic mixing device has integrated valves and pumps to accurately accomplish titration of biomolecules with picoliter resolution. We demonstrate that the approach enabled rapid sampling of biomolecule conformational landscape and of enzymatic activity, in the form of transcription by Escherichia coli RNA polymerase, as a function of the chemical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 23 publications
0
114
0
Order By: Relevance
“…RP O is then incubated in solution at 37°C for 30 min. To remove unreacted and nonspecifically bound RNAP, 1 μL of 100 mg/mL Heparin-Sepharose CL-6B beads (GE Healthcare) is added to RP O solution together with 10 μL of prewarmed 1× transcription buffer [Heparin challenge (3,65)]. The mixture is incubated for 1 min at 37°C and centrifuged for at least 45 s at 6,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…RP O is then incubated in solution at 37°C for 30 min. To remove unreacted and nonspecifically bound RNAP, 1 μL of 100 mg/mL Heparin-Sepharose CL-6B beads (GE Healthcare) is added to RP O solution together with 10 μL of prewarmed 1× transcription buffer [Heparin challenge (3,65)]. The mixture is incubated for 1 min at 37°C and centrifuged for at least 45 s at 6,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…9B also shows data points from a series of quenched kinetics experiments red square), obtained with the same system but a completely different experimental strategy (see ref. [43] for details). In this approach, a doubly-labeled complementary ssDNA probe hybridizes with the RNA transcript once the transcription reaction is stopped after a specified reaction time t. Hybridization of the probe results in a shift from high to low FRET.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture was incubated for 5 min at 37 ºC and centrifuged for at least 45 s at 6,000 rpm. 20 μl of the supernatant containing RPO wass transferred into a new tube containing 10 μl of pre-warmed 1X transcription buffer (heparin challenge [43,44]). …”
Section: Multispot Fcs Analysis Resultsmentioning
confidence: 99%
“…9,14,18,[37][38][39][40][41][42][43][44] Recently, using different experimental approaches, Duchi et al 1 and Lerner, Chung et al 2 have provided direct evidence of E. coli RNAP transcription pausing during initiation at a modified lac promoter, lacCONS. 45 Lerner, Chung et al measured the kinetics of single-round transcription reactions with unlabeled reconstituted RNAP holoenzyme and promoter DNA free in solution. They observed that formation of a full-length transcript starting from a late initiation stage (e.g., initially transcribing RNAP promoter complex, ITC, synthesizing abortive transcripts of up to 7 nucleotides (nt) in length, RP ITC 7 ) was delayed as compared with transcription starting from early initiation stages (order of delays: RP ITC 7 > RP ITC 6 > RP ITC 4 > RP ITC D 2 ).…”
Section: Experimental Evidence Of Pausing During Transcription Initiamentioning
confidence: 99%